The Effect of Work Motivation, Work Discipline and Work Environment on Employee Performance at PT Sport Glove Indonesia - Fernanda, Olivia; Tasrim, Tasrim (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The point of this study is to look into how work motivation, work discipline, and the work setting at PT Sport Glove Indonesia affect how well employees do their jobs. Using a quantitative method, the study uses first-hand information gathered from surveys sent to employees in different departments. To test the assumptions, multiple regression analysis was done.As shown by a positive regression coefficient and a t-test value above the critical level, The findings demonstrate that employee performance is positively and significantly impacted by work motivation. Similarly, there is a strong and positive correlation between employee performance and job discipline. This shows how important it is to follow company rules and be on time in order to reach organizational goals. In addition,The workplace has a positive and noteworthy impact, which suggests that a supportive and pleasant workplace makes workers more productive. These results make it clear that PT Sport Glove Indonesia needs to put a high priority on programs that boost motivation, tighten up discipline, and make the workplace a good place to work so that employees can do their best work. The study adds to what is known about company behavior and gives managers useful information they can use to make their workers more productive.